Revisão narrativa da literatura sobre o impacto dos influenciadores digitais nas organizações - Rabachini, Graziela Akassaka (Universidade Federal de São Carlos, 2025)
Social media has profoundly transformed organizational communication strategies, especially with the rise of digital influencers. This study aims to analyze the impact of digital influencers on organizations based on a narrative literature review of academic publications from 2013 to 2025. By examining 18 scientific articles, the research identifies the main benefits and challenges associated with the role of influencers in organizational strategies. Among the positive factors observed are the strengthening of brand credibility, increased audience engagement and reach, direct influence on purchasing decisions, the production of authentic content, and positive effects on financial performance and organizational outcomes. Additionally, the study highlights the growing presence of influencer marketing in B2B contexts, the emergence of artificial intelligence influencers, and the potential of influencers to promote social values and positive behaviors. On the other hand, several risks and challenges were identified, such as loss of authenticity, difficulties in measuring return on investment, lack of regulation, brand reputation risks, and market saturation. The study concludes that the use of digital influencers must be strategically planned and ethically conducted, ensuring alignment between the brand, influencer, and target audience in order to maximize benefits and mitigate associated risks.
Narrative Literature Review on the Impact of Digital Influencers on Organizations
Keywords: Influenciadores Digitais; Marketing de Influência; Mídias Sociais; Organizações; Revisão Narrativa; Digital Influencers; Influencer Marketing; Social Media; Organizations; Narrative Review; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO